Where are we now? Socio-ecological risks and community responses to oil and gas development in Colorado - Boone, Karie, author; Laituri, Melinda, author; Colorado Water Institute, publisher (Colorado State University. Libraries, 2016)
Colorado is the sixth largest gas-to-market producer in the nation, situating the state for substantial impact on energy resources at a national scale. The increase in pace and scale of oil and gas development over the last five to seven years can be attributed to technological advances in the process of hydraulic fracturing (HF) and horizontal drilling, favorable market prices, and an investment in long-term federally funded research aimed at nationalizing energy resources. However, the potential of multiple and contested risks related to HF have led to increases in community activism across Colorado. This report examines community responses to the increased pace and scale of oil and natural gas development in Pennsylvania and Colorado. Grassroots organizations and citizens are concerned with the potential air emissions, water use, economic, and socio-psychological risks associated with the energy development known as "fracking." An assessment of peer-reviewed literature on these potential risks is presented. Through a review of the most recent peer-reviewed scholarly research and government reports, this paper additionally examines the socio-ecological risks confronted in Pennsylvania and Colorado, and to a lesser extent Wyoming and Texas, as part of developing energy on a large scale. This section begins with a review of economic benefits and challenges of oil and gas development. Input-output models are an important tool for projecting economic impacts at multiple scales. However, much of the literature in this realm critiques the assumptions on which input-output models are based, including exclusion of environmental and social externalities as well as temporal aspects of resource-dependent economies. This is followed by an examination of Lifecycle Analyses (LCAs), the preferred methodological tool for scientists measuring air emissions. LCAs have the utility of not only documenting the full time span of natural gas emissions, but also providing policy-makers with a standard format for energy portfolio decision-making. A review of the research on socio-psychological health concerns and air emissions is provided. In addition to the full lifecycle studies, regional Health Impact Assessments (HIAs) have been carried out to measure the risk of air emissions near the site of extraction and the potential harm caused to nearby communities. The HIAs were carried out both on the Front Range and the Western Slope of Colorado. These quantitative-based studies are followed by a qualitative analysis of the everyday socio-psychological health impacts that accompany rapid environmental changes and industrialization of the rural countryside with oil and gas development. Residents recount their experiences with a changing social, environmental, and political landscape. In addition, this report reviews 20 studies that highlight the probable linkages between contamination of ground and surface waters with hydraulic fracturing activities. There is controversy and debate between university academics, industry, and hired consultancy firms over the validity of these linkages. One of these debates is examined, followed by a discussion of the contradictory and complicated contexts within which citizens and policy-makers must take action.
Date inferred by cataloger, series and number taken from website.
Keywords: oil and gas; Colorado; community responses; grassroots; water contamination; air emissions; hydraulic fracturing